Oncological outcomes and recurrence patterns after laparoscopic radical cystectomy for bladder cancer: A Japanese multicenter cohort. (16th January 2020) - Kanno, Toru; Inoue, Takahiro; Ito, Katsuhiro; Okumura, Kazuhiro; Yamada, Hitoshi; Kawakita, Mutsushi; Fujii, Masato; Shimizu, Yosuke; Yatsuda, Junji; Moroi, Seiji; Shichiri, Yasumasa; Akao, Toshiya; et al.
Abstract : Objective: To investigate oncological outcomes and recurrence patterns after laparoscopic radical cystectomy for bladder cancer in a Japanese multicenter cohort, and to explore the risk factors associated with recurrences due to tumor dissemination. Method: Laparoscopic radical cystectomies carried out at 10 institutions were included in this retrospective study. Multivariate analyses were carried out to identify the clinical parameters associated with overall recurrences together with specific recurrence types. Kaplan–Meier curves were created to elucidate time to recurrence and survival. Results: A total of 411 patients were included after the final analysis. Postoperative pathology was T2 or higher in 196 patients (48%), and lymph node metastasis was present in 46 patients (11%). The median follow‐up period was 23 months, and the 2‐year recurrence‐free and cancer‐specific survival rates were 71.0% and 84.7%, respectively. The recurrence sites involved distant metastasis in 75 patients (18%), local recurrence in 52 patients (13%) and urinary tract recurrence in eight patients (2%). When local recurrence at the cystectomy bed (28 patients; 7%) and abdominal recurrence including peritoneal carcinomatosis or port site recurrence (17 patients; 4%), which might be caused by tumor dissemination, were combined into a single group, prolonged surgical time was a significant risk factor, in addition to high pathological stage (T3–4 and/or positive lymph nodes), positive surgical margins, and variant histology by both univariate and multivariate analyses. Conclusions: Our study findings suggest that recurrences after laparoscopic radical cystectomy might be caused by tumor dissemination, and attention should be paid to avoid prolonged surgical time in laparoscopic radical cystectomy.